Integrated Farmer-Livestock Business In Opaasi Village, West Ranomeeto District, South Konawe Regency - Laode Muh Munadi; Natsir Sandiah; Achmad Selamet Aku; Rahim Aka; Astriana Napirah; La Ode Muh Munadi (International Journal Of Community Service, 2022)
The potential for the development of beef cattle farming in South Konawe Regency is a potential area for the development of Bali cattle with a beef cattle population of 367,665 heads and one of them is Ranomeeto Barat District with a cattle population of 3608 heads or 5.01% of the total population in the Regency. South Konawe. The purpose of this service is to provide technical assistance and guidance, as well as training in increasing knowledge and skills regarding potential, preparing livestock business plans, and overcoming problems faced by farmers with the methods used including the preparation stage, socialization stage, and activity implementation stage. The results of community service in technical assistance and training in making colony cages, making compost, preparing livestock business plans provide an alternative for the community in maximizing the productivity of beef cattle business.